Immunogenicity of COVID-19 Tozinameran Vaccination in Patients on Chronic Dialysis - Schrezenmeier, Eva; Bergfeld, Leon; Hillus, David; Lippert, Joerg-Detlev; Weber, Ulrike; Tober-Lau, Pinkus; Landgraf, Irmgard; Schwarz, Tatjana; Kappert, Kai; Stefanski, Ana-Luisa; Sattler, Arne; Kotsch, Katja; et al. (Frontiers in Immunology, 2021)
Patients with kidney failure have notoriously weak responses to common vaccines. Thus, immunogenicity of novel SARS-CoV-2 vaccines might be impaired in this group. To determine immunogenicity of SARS-CoV-2 vaccination in patients with chronic dialysis, we analyzed the humoral and T-cell response after two doses of mRNA vaccine Tozinameran (BNT162b2 BioNTech/Pfizer). This observational study included 43 patients on dialysis before vaccination with two doses of Tozinameran 21 days apart. Overall, 36 patients completed the observation period until three weeks after the second dose and 32 patients were further analyzed at week 10. Serum samples were analyzed by SARS-CoV-2 specific IgG and IgA antibodies 1, 3–4 and 10 weeks after the second vaccination. In addition, SARS-CoV-2-specific T-cell responses were assessed at 3–4 weeks by an interferon-gamma release assay (IGRA). Antibody and T cell outcomes at this timepoint were compared to a group of 44 elderly patients not on dialysis, after immunization with Tozinameran. Median age of patients on chronic dialysis was 74.0 years (IQR 66.0, 82.0). The proportion of males was higher (69.4%) than females. Only 20/36 patients (55.6%, 95%CI: 38.29–71.67) developed SARS-CoV-2-IgG antibodies at the first sampling, whereas 32/36 patients (88.9%, 95%CI: 73.00–96.38) demonstrated IgG detection at the second sampling. In a longitudinal follow-up at 10 weeks after the second dose, the proportion of dialysis patients reactive for anti-SARS-CoV-2-IgG decreased to 27/32 (84.37%, 95%CI: 66.46–94.10) The proportion of anti-SARS-CoV-2 S1 IgA decreased from 33/36 (91.67%; 95%CI: 76.41–97.82) at weeks 3–4 down to 19/32 (59.38; 95%CI: 40.79–75.78). Compared to a cohort of vaccinees with similar age but not on chronic dialysis seroconversion rates and antibody titers were significantly lower. SARS-CoV-2-specific T-cell responses 3 weeks after second vaccination were detected in 21/31 vaccinated dialysis patients (67.7%, 95%CI: 48.53–82.68) compared to 42/44 (93.3%, 95%CI: 76.49–98.84) in controls of similar age. Patients on dialysis demonstrate a delayed, but robust immune response three to four weeks after the second dose, which indicates effective vaccination of this vulnerable group. However, the lower immunogenicity of Tozinameran in these patients needs further attention to develop potential countermeasures such as an additional booster vaccination.